ANXA1 Enhances the Proangiogenic Potential of Human Dental Pulp Stem Cells - Xiaocao Ma; Bichun Zhao; Chao Wang; Manqiang Sun; Yawen Dai; Lingling E.; Mingzhu Gao; Xiangwei Liu; Yali Jia; Wen Yue; Hongchen Liu (Stem Cells International)
Dental trauma is highly prevalent in children and adolescents, alongside tooth decay. This condition mainly induces pulp contamination, pulp necrosis, and tooth avulsion in the clinical context. The disturbance to root growth is prone to occur in immature permanent teeth. However, conventional endodontic treatment may not achieve favorable outcomes in these cases, necessitating conducting relevant exploration. Therefore, this study was performed to examine the impact of Annexin A1 (ANXA1) on the vascular repair of dental pulp using human dental pulp stem cells (DPSCs). Specifically, RNA sequencing (RNA-Seq) and functional clustering analyses were employed to identify key genes involved in pulp regeneration. ANXA1 was detected in DPSCs and may correlate with pulp restoration. However, it remains undefined about the potential of ANXA1 to promote the angiogenetic differentiation of DPSCs. The results of this study revealed that the addition of ANXA1 significantly enhanced the secretion of vascular endothelial growth factor-A (VEGF-A) in DPSCs. Moreover, the incubation of DPSCs with ANXA1 resulted in a higher expression level of endothelial markers and promoted vessel formation through the upregulation of the phosphorylated p38 (p-p38) pathway. The in vivo results corroborated that the ANXA1 group exhibited more blood vessels and an increased ratio of positive staining for CD31. In conclusion, these findings indicate that ANXA1 enhances the in vivo and in vitro vascularization of DPSCs, and the activation of p-p38 may play a pivotal role in mediating the differentiation process.